Pendekatan Semiotika Untuk Penulisan Sejarah: Beberapa Kemungkinan - Angga Pusaka Hidayat (Tsaqofah, 2021)
Historical writing is growing in terms of themes, objects of study, sources, methods, and methodologies. The presence of novelty in historical writing demands a relatively new approach. Writing history as a representation of a series of historical research processes is actually the fruit of the process of interpreting all traces/evidence that has arrived at historians. The growing use of visual sources among historians simultaneously requires that historians have the tools to interpret these sources. Approach that can be used in interpreting this visual source is the semiotic approach. Concepts in semiotics, inter alia, the bilateral concept of sign: signifier and signified and denotationconnotation are very useful to be used as analytical tools and help develop explanations. The development of the history of appearance has also become another way for the use of a semiotic approach in historical writing. The dimension of semiotics is expected to be able to further confirm the nature of history in interpreting, explanating and understanding.